2018
DOI: 10.1371/journal.pone.0190476
|View full text |Cite
|
Sign up to set email alerts
|

Classification of rare land cover types: Distinguishing annual and perennial crops in an agricultural catchment in South Korea

Abstract: Many environmental data are inherently imbalanced, with some majority land use and land cover types dominating over rare ones. In cultivated ecosystems minority classes are often the target as they might indicate a beginning land use change. Most standard classifiers perform best on a balanced distribution of classes, and fail to detect minority classes. We used the synthetic minority oversampling technique (smote) with Random Forest to classify land cover classes in a small agricultural catchment in South Kor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…However, several previous studies reported results consistent with our findings. Reference [25] reported an increase in F-score and G-mean when oversampling was applied, while Accuracy did not improve. Similarly, results obtained in [5] demonstrated increased classification performance when using SMOTE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several previous studies reported results consistent with our findings. Reference [25] reported an increase in F-score and G-mean when oversampling was applied, while Accuracy did not improve. Similarly, results obtained in [5] demonstrated increased classification performance when using SMOTE.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the application of SMOTE improved the classification results. Other examples of the successful application of SMOTE in remote sensing can be found in [25,26].…”
Section: Informed Resamplingmentioning
confidence: 99%
“…Once collected, the samples were statistically filtered (with the 80th percentile function) and visually inspected to remove inadequate training samples. Stratified sampling and statistical filtering are necessary to address imbalanced class problems [50], allowing the removal of outliers from the sample bag. The presence of imbalanced Having set the refined training region,~1000 stratified random samples were distributed per class, mangrove and non-mangrove, per sector per year.…”
Section: Methodsmentioning
confidence: 99%
“…Stratified sampling and statistical filtering are necessary to address imbalanced class problems [50], allowing the removal of outliers from the sample bag. The presence of imbalanced classes within the coastal region is a probable scenario, as water surface samples may, in general, greatly surpass other rare class occurrences (e.g., mangrove cover).…”
Section: Methodsmentioning
confidence: 99%
“…It should be also noted that no training/test samples from the cloud-contaminated parts of the 50 cm image were collected, because the underlying LULC types were not apparent in those areas. Since the training data gathered for both the images were imbalanced, we applied the Synthetic Minority Oversampling Technique (SMOTE) [54] to artificially balance the training set, as this was found beneficial in past studies using imbalanced data [55,56] and machine learning classifiers [57].…”
Section: Each Of the Computed Features Was Then Standardized (To Havementioning
confidence: 99%